광주광역시 1개 치과병원 내원환자의 주관적 구강건강인식과 구강건강상태 관련성 - 이병진; Byoungjin Lee; 김승희; Seunghee Kim (대한구강보건학회지, 2020)
Objectives: The purposes of the present study were to (1) analyze the relationship between clinical oral health status and subjective oral health status, (2) explore the association between perceived oral symptoms and subjective oral health status, and (3) investigate the effects of factors on subjective oral health status. Methods: A total of 771 subjects, aged over 35 years of age, from a dental hospital in Gwangju metropolitan city, were surveyed cross-sectionally using a self-report questionnaire. We investigated the relationship of subjective oral health status with clinical oral health status, and with perceived oral symptoms using a Chi-squared test (P<0.05). To investigate the effects of factors on subjective oral health status relationship, a logistic regression analysis was performed. Results: The odds ratios of subjective oral health status between ‘Bad’ vs ‘Good’ were as follows: frequent oral concern, 43.41; occasional oral concern, 2.94; toothache, 6.08; hypersensitivity to coldness, 2.13; 1-3 year’s periodic preventive oral care, 0.19; 4-7 and periodic preventive oral care, 0.14. Conclusions: Periodic preventive oral care appears to be associated with self-rated subjective oral health status.